A survey of augmentative and alternative communication used in an inner city special school. (23rd September 2016) - Norburn, Katie; Levin, Abigail; Morgan, Sally; Harding, Celia
Abstract : This study surveyed staff use of augmentative and alternative communication (AAC) within a large inner city special school for children with complex needs and learning disabilities. A questionnaire asked 72 staff members about the range of AAC strategies they typically used during the working day and how often they used it; training they had received about AAC; and which AAC approaches they found easy to use and those they found difficult. A range of AAC approaches were identified by staff. Participant confidence and understanding of the reasons for using identified AAC strategies was reported to be one of the key barriers to implementing AAC effectively. The implications in relation to how children with complex needs receive support for their receptive and expressive communication within an education environment are discussed.